Wireless ad hoc and sensor networks management, performance, and applications - He, Jing Selena (CRC Press, Taylor & Francis Group, 2014)
"Although wireless sensor networks (WSNs) have been employed across a wide range of applications, there are very few books that emphasize the algorithm description, performance analysis, and applications of network management techniques in WSNs. Filling this need, Wireless Ad Hoc and Sensor Networks: Management, Performance, and Applications summarizes not only traditional and classical network management techniques, but also state-of-the-art techniques in this area. The articles presented are expository, but scholarly in nature, including the appropriate history background, a review of current thinking on the topic, and a discussion of unsolved problems. The book is organized into three sections. Section I introduces the basic concepts of WSNs and their applications, followed by the summarization of the network management techniques used in WSNs. Section II begins by examining virtual backbone-based network management techniques. It points out some of the drawbacks in classical and existing methods and proposes several new network management techniques for WSNs that can address the shortcomings of existing methods. Each chapter in this section examines a new network management technique and includes an introduction, literature review, network model, algorithm description, theoretical analysis, and conclusion. Section III applies proposed new techniques to some important applications in WSNs including routing, data collection, data aggregation, and query processing. It also conducts simulations to verify the performance of the proposed techniques. Each chapter in this section examines a particular application using the following structure: brief application overview, application design and implementation, performance analysis, simulation settings, and comments for different test cases/scenario configurations"--
Includes bibliographical references and index. - Print version record
Keywords: Wireless sensor networks; Ad hoc networks (Computer networks); Réseaux de capteurs sans fil; Réseaux ad hoc (Réseaux d'ordinateurs); COMPUTERS; Networking; General; TECHNOLOGY & ENGINEERING; Mobile & Wireless Communications; COMPUTERS; Data Transmission Systems; General; COMPUTERS; Networking; Vendor Specific